Building situational stimuli in assessment center exercises: Do specific exercise instructions and role-player prompts increase the observability of behavior? - SCHOLLAERT, Eveline (Institutional Knowledge at Singapore Management University, 2012)
Little is known about how assessment center exercises might be designed to better elicit job-relevant behavior. This study uses trait activation theory as a theoretical lens for increasing the number of behaviors that can be observed in assessment centers. Two standardized exercise stimuli (specific exercise instructions and role-player prompts) are proposed, and their effects on the observability of candidate behavior are examined. Results showed a significant effect of role-player prompts in increasing both the general number of behavioral observations and the number of behavioral observations related to three out of four dimensions. Specific exercise instructions did not have effects on observability. Implications for trait activation theory and assessment center practice are discussed.